2013
DOI: 10.1073/pnas.1310745110
|View full text |Cite
|
Sign up to set email alerts
|

Greatwall is essential to prevent mitotic collapse after nuclear envelope breakdown in mammals

Abstract: Significance Nuclear envelope breakdown (NEB) leads to the exposure of nuclear structures to cytoplasmic activities. Greatwall is a kinase able to inhibit PP2A phosphatases that counteract Cdk-dependent phosphorylation required for mitosis. Here we show that Greatwall, an essential protein in mammals, is exported to the cytoplasm in a Cdk-dependent manner before NEB, thus protecting mitotic phosphates from phosphatase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
170
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(190 citation statements)
references
References 27 publications
17
170
1
2
Order By: Relevance
“…This finding is in agreement with previous studies in human and Drosophila that reported nuclear export of Gwl before nuclear membrane breakdown. 15,20 However, distinct from the previous study that suggested a requirement of Gwl kinase activity for its nuclear export, 20 we found a similar pattern of nucleocytoplasmic relocalization for G41S Gwl prior to mitotic entry (Fig. 4B).…”
Section: Dynamic Nucleocytoplasmic Localization Of Gwl During the Celsupporting
(Expert classified)
See 4 more Smart Citations
“…This finding is in agreement with previous studies in human and Drosophila that reported nuclear export of Gwl before nuclear membrane breakdown. 15,20 However, distinct from the previous study that suggested a requirement of Gwl kinase activity for its nuclear export, 20 we found a similar pattern of nucleocytoplasmic relocalization for G41S Gwl prior to mitotic entry (Fig. 4B).…”
Section: Dynamic Nucleocytoplasmic Localization Of Gwl During the Celsupporting
(Expert classified)
“…15,20 We also observed in Xenopus cells that nuclear Gwl started to diffuse into cytoplasm before centrosomes reached opposite positions. While it remained unclear how this nucleocytoplasmic translocation of Gwl may contribute to the regulation of mitotic entry, previous studies indicated that the translocation was dependent on Gwl phosphorylation by CDK1, and possibly also Plk1.…”
Section: Dynamic Nucleocytoplasmic Localization Of Gwl During the Celmentioning
confidence: 63%
See 3 more Smart Citations